Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{1}{1-x}+\dfrac{1}{1+x}+\dfrac{2}{1+x^2}+\dfrac{4}{1+x^4}+\dfrac{8}{1+x^8}+\dfrac{16}{1+x^{16}}\)
\(=\dfrac{1+x+1-x}{1-x^2}+\dfrac{2}{1+x^2}+\dfrac{4}{1+x^4}+\dfrac{8}{1+x^8}+\dfrac{16}{1+x^{16}}\)
\(=\dfrac{2+2x^2+2-2x^2}{1-x^4}+\dfrac{4}{1+x^4}+\dfrac{8}{1+x^8}+\dfrac{16}{1+x^{16}}\)
\(=\dfrac{4+4x^4+4-4x^4}{1-x^8}+\dfrac{8}{1+x^8}+\dfrac{16}{1+x^{16}}\)
\(=\dfrac{8+8x^8+8-8x^8}{1-x^{16}}+\dfrac{16}{1+x^{16}}\)
\(=\dfrac{16+16x^{16}+16-16x^{16}}{1-x^{32}}=\dfrac{32}{1-x^{32}}\)
\(\dfrac{1}{x-1}-\dfrac{1}{x+1}-\dfrac{2}{x^2+1}-\dfrac{4}{x^4+1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)
\(=\dfrac{x+1-x+1}{x^2-1}-\dfrac{2}{x^2+1}-\dfrac{4}{x^4+1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)
\(=\dfrac{2}{x^2-1}-\dfrac{2}{x^2+1}-\dfrac{4}{x^4+1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)
\(=\dfrac{2\left(x^2+1-x^2+1\right)}{x^4-1}-\dfrac{4}{x^4+1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)
\(=\dfrac{4}{x^4-1}-\dfrac{4}{x^4+1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)
\(=\dfrac{4\left(x^4+1-x^4+1\right)}{x^8-1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)
\(=\dfrac{8}{x^8-1}-\dfrac{8}{x^8+1}-\dfrac{16}{x^{16}+1}\)
\(=\dfrac{8\left(x^8+1-x^8+1\right)}{x^{16}-1}-\dfrac{16}{x^{16}+1}\)
\(=\dfrac{16}{x^{16}-1}-\dfrac{16}{x^{16}+1}\)
\(=\dfrac{16\left(x^{16}+1-x^{16}+1\right)}{x^{32}-1}\)
\(=\dfrac{32}{x^{32}-1}\)
\(\frac{x+1}{x-1}-\frac{x-1}{x+1}=\frac{16}{x^2-1}ĐK:x\ne\pm1\)
\(\Leftrightarrow\frac{\left(x+1\right)^2}{\left(x-1\right)\left(x+1\right)}-\frac{\left(x-1\right)^2}{\left(x-1\right)\left(x+1\right)}=\frac{16}{\left(x-1\right)\left(x+1\right)}\)
\(\Leftrightarrow x^2+2x+1-x^2+2x-1=16\Leftrightarrow4x=16\Leftrightarrow x=4\)( tmđk )
Vậy tập nghiệm của phương trình là S = { 4 }